Hybrid Terrorism and Organized Crime Networks in the Asia-Pacific Region: Examining the Links between Cybercrime and Violent Extremism. - Odeh, Emmanuel Ejike; Onwo, Desmond; Ogbuka, Ikenna; Duru, Innocent (Journal Of Social And Political Science, 2025)
Hybrid terrorism and organized crime networks have become serious security threats in the Asia-Pacific region, with cybercrime playing an increasingly prominent role in funding and spreading their violent extremist activities. Long-running illicit activities in the area by organized crime groups include the trafficking of drugs, the smuggling of people, and money laundering. This paper examines the links between cybercrime and violent extremism, highlighting the use of social media and other online platforms by organized crime networks and the radicalization of violent extremism in the Asia-Pacific region. The paper based its theoretical framework on social learning theory, and an ex-post facto research design was adopted, while its methods of data collection were documentary and survey. Content and qualitative analysis were utilized to analyze the data obtained. The extensive use of social media and other online platforms by organized crime networks has been found to be a significant factor in the growing trend of violent extremism in the Asia-Pacific region. It is recommended that governments and law enforcement agencies engage in proactive monitoring and take the necessary measures to combat these hybrid networks.